Hes1 Desynchronizes Differentiation of Pluripotent Cells by Modulating STAT3 Activity1. (23rd August 2013) - Zhou, Xinzhi; Smith, Andrew J.H.; Waterhouse, Anna; Blin, Guillaume; Malaguti, Mattias; Lin, Chia‐Yi; Osorno, Rodrigo; Chambers, Ian; Lowell, Sally
Abstract Robust development of the early embryo may benefit from mechanisms that ensure that not all pluripotent cells differentiate at exactly the same time: such mechanisms would build flexibility into the process of lineage allocation. This idea is supported by the observation that pluripotent stem cells differentiate at different rates in vitro. We use a clonal commitment assay to confirm that pluripotent cells commit to differentiate asynchronously even under uniform differentiation conditions. Stochastic variability in expression of the Notch target gene Hes1 has previously been reported to influence neural versus mesodermal differentiation through modulation of Notch activity. Here we report that Hes1 also has an earlier role to delay exit from the pluripotent state into all lineages. The early function of Hes1 to delay differentiation can be explained by an ability of Hes1 to amplify STAT3 responsiveness in a cell‐autonomous manner. Variability in Hes1 expression therefore helps to explain why STAT3 responsiveness varies between individual ES cells, and this in turn helps to explain why pluripotent cells commit to differentiate asynchronously. STEM Cells 2013;31:1511–1522